Model Bangkitan Perjalanan Kerja dan Faktor Aksesibilitas pada Zona Perumahan di Yogyakarta - Yuswendra Ersandi; Ahmad Munawar; Sri Atmaja P Rosyidi (Semesta Teknika, 2009)
The aim of this paper is to develop the mathematical model of home based work-trip generation and to obtain its trip variables influencing the model. Factors of trip accessibility i.e. distance to work, travel time, cost for public transport and cost for private vehicle were also observed in the model. In this study, several households in Griya Taman Asri, Sleman Yogyakarta were chosen for questioner sample in home interview survey. Mathematical model was generated using the multi-linear regression with the dependent variable is work-trip which is affected by nine independent variables. The generated model was then validated by VIF and Anova test. The result shows that the work-trip generation model for Griya Taman Asri was influenced by parameter of the car ownership (X2) and the worker in household (X5). However, all trip accessibility factors considered in this study do not influence to work-trips.